THE USE OF PROBLEM BASED LEARNING TO INCREASE STUDENTS’ LEARNING INDEPENDENT AND TO INVESTIGATE STUDENTS’ CONCEPT UNDERSTANDING ON ROTATIONAL DYNAMIC AT STUDENTS OF SMA NEGERI 4 BANDA ACEH - Haji, A. G.; Safriana, S.; Safitri, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
The objective of this study is to find out the increase in student’s independent learning and concept understanding on the rotational dynamics after getting the PBL learning and handout. This study was conducted by using